PENGARUH LABA AKUNTANSI, ARUS KAS OPERASI, LIKUIDITAS DAN PROFITABILITAS TERHADAP RETURN SAHAM - Tigau, Gideon (AKRUAL : Jurnal Akuntansi dan Keuangan, 2025)
The purpose of this study is to determine how accounting profit, operating cash flow, liquidity, and profitability affect stock returns in primary consumer goods manufacturing companies listed on the IDX during 2021-2023. This type of research uses a quantitative associative research method. All primary consumer goods manufacturing companies listed on the IDX for the period 2021-2023 are the population in this study. The sampling technique in this study used a purposive sampling technique which produced a sample of 34 companies in a 3-year period, resulting in a sample of 102. Data were collected by examining the company's financial statements using a documentation observation approach. Panel data regression is the data analysis strategy used in this study, with the help of Eviews 12 software. The results obtained show that stock returns are positively influenced by accounting profit while operating cash flow, liquidity and profitability do not affect stock returns.